Association between the composite dietary antioxidant index and cardiovascular-kidney-metabolic syndrome among U.S. adults: evidence from NHANES 2007–2018 - He, Qiuming; Hu, Fan; Wei, Wanhui; Li, Jie; Yu, Yang; Zhang, Heng (Frontiers in Nutrition, 2025)
ObjectiveCardiovascular-kidney-metabolic (CKM) syndrome is a major public health issue worldwide. However, direct evidence on dietary modulators in CKM syndrome is lacking. This study aimed to explore the association between the Composite Dietary Antioxidant Index (CDAI) and advanced CKM syndrome using National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018.MethodsAdvanced CKM syndrome (Stage 3–4) was defined using 2023 AHA criteria. CDAI was calculated from averaged 24-h dietary recalls for six antioxidants (vitamins A/C/E, zinc, selenium, carotenoids). Weighted multivariable logistic regression adjusted for sociodemographics, lifestyle, and metabolic factors. Multinomial logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CI), adjusting for potential confounders. Furthermore, restricted cubic splines (RCS) were applied to investigate any possible nonlinear relationships between CDAI and CKM syndrome in the study.ResultsThis study included 11,073 adults aged 20 years and older, with a mean age of 48 years and a gender distribution of 52.75% female and 47.25% male. Multivariate logistic regression with full adjustment for covariates showed that higher CDAI scores were inversely associated with advanced CKM syndrome. Specifically, compared to the lowest quartile, the highest quartile of CDAI scores had an OR of 0.70 (95% CI: 0.49–0.98). A nonlinear negative correlation was identified by the RCS (p for nonlinearity = 0.031). In both the subgroup and sensitivity analysis, this relationship was still present.ConclusionHigher CDAI scores are correlated with decreased odds of advanced CKM syndrome, suggesting that an antioxidant-rich diet may be associated with a lower likelihood of advanced CKM syndrome. Understanding these correlations could contribute to the development of preventive strategies and intervention measures for CKM syndrome. However, prospective studies are needed to confirm these associations and explore their clinical relevance.